Information and Communication Technology for Disaster Risk Management in Japan : How Digital Solutions are Leveraged to Increase Resilience through Improving Early Warnings and Disaster Information Sharing - World Bank (World Bank, Washington, DC, 2019)
Breakthroughs in information and communication technology (ICT) increasingly offer new tools to support disaster risk management (DRM). Due to the rapid advancement of computing and communication devices, ICT’s capacity to improve the DRM framework became a critical factor to strengthen resilience. As a nation with high levels of disaster risk and technological development, Japan has developed several forward-looking ICT for DRM. This report highlights the application of ICT for DRM in two specific areas: Early Warning System (EWS) and Disaster Information Management System (DIMS). The analysis of eight Japanese case studies of ICT solutions for DRM across various sectors, hazards, and levels of governance gives insight into their development, selection process and enabling environments, and provides case-specific lessons and recommendations. This report is intended as a reference tool for global DRM practitioners seeking to develop an enabling environment for applying ICT solutions toward resilience. The lessons learned from the Japanese case studies are intended to support practitioners and decision-makers in other countries to envision and explore ways to better leverage ICT to strengthen resilience. While valuable information can be extracted from the analysis, each case is contextualized within its particular social, political and environmental framework: our recommendations should be adapted to local needs and capacities.